Patterning of titanium oxide nanostructures by electron-beam lithography combined with plasma etching. (8th June 2015) - Hotovy, I; Kostic, I; Nemec, P; Predanocy, M; Rehacek, V
Abstract: Patterning of metal oxide nanostructures with precisely controlled geometries and spacings can play an important role in the improvement of sensors for gas detection. Titanium oxide thin films were deposited on oxidized silicon substrates by reactive magnetron sputtering at room temperature. Patterning of TiO2 nanostructures was conducted by electron beam lithography combined with plasma etching. It was found that for 120 nm-thick TiO2 nanostructure formation, HSQ e-beam resists and Cr films prove to be suitable mask materials. Experimental results showed that the size of TiO2 nanostructures depends mainly on the e-beam lithography process and they can be controlled by the design geometry and the exposure dose. TiO2 nanostructures with a minimal diameter of 70 nm and spacing of 200 nm were successfully fabricated by ICP etching in CF4 /Ar plasma through negative e-beam resist HSQ.